Usage, anti-inflammatory effect and safety of adjunctive acupuncture for cerebral infarction: an Apriori algorithm-based data mining and meta-analysis - Fangfei Yu; Shuang Li; Zunjiang Li; Zunjiang Li; Zunjiang Li; Zhaofan Mo; Rong Liu; Jiaying Zhao; Banghan Ding; Banghan Ding; Wei Yi; Wei Yi; et al. (Frontiers in Neurology)
Background purposeThe adjunctive effect of acupuncture for cerebral infarction (CI) remains inconsistent. We aimed to determine its anti-inflammatory effect, assess safety, and summarize the adjunctive use of acupuncture for CI.MethodsWe identified qualified randomized controlled trials (RCTs) from eight literature databases. Frequency analysis and Apriori association analysis were conducted using SPSS Modeler 18.0 and SPSS 26.0 software. A meta-analysis was performed using Stata 17.0 software. The credibility of the meta-results and the certainty of the evidence was assessed using trial sequential analysis (TSA) and GRADE methods, respectively.ResultsA total of 43 RCTs were included, comprising 3,861 participants. Acupuncture with intermittent treatment (5–7 times per week), a combination of multiple points and multiple meridians (an average of 9.35 points in each prescription), typically lasting for 2–4 weeks, was commonly used for CI treatment. Meta-analysis indicated that the adjunctive use of acupuncture reduced levels of TNF-α (SMD = −1.36; 95% CI −1.51 to −1.20, p < 0.01), hs-CRP (SMD = −0.86; 95% CI −0.99 to −0.74, p < 0.01), and IL-6 (SMD = −0.85; 95% CI −1.08 to −0.62, p < 0.01), and decreased the rate of adverse events (RR = 0.71; 95% CI 0.49 to 1.01; p < 0.05). The certainty of the evidence was rated as moderate to high.ConclusionIntermittent acupuncture treatment lasting at least 2 w was commonly used for CI patients, typically involving multiple acupuncture points and meridians. Acupuncture demonstrated an anti-inflammatory effect in the treatment of CI. However, due to the low quality of the existing literature, high-quality randomized controlled trials (RCTs) are required to confirm these results in the future.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42017078583.